EESEE 2024: 9th Electrical Electronics Systems Engineering Exhibition 2024; volume 1 / Noor Hafizah Khairul Anuar ... [et al.] - Anuar, Noor Hafizah Khairul Anuar (School of Electricall Engineering, 2024)
The platform is for the students to present their project as it is a critical turning point in their academic careers, which are the result of years of effort and commitment and a major step toward earning their diplomas. This year's project themes focus on the Internet of Things (IoT) including Industrial Revolution 4.0. These books highlight our students' exceptional work, which shows off not only their technical proficiency but also their ability to engage meaningfully with professionals and other students. You will come across a wide range of projects in this long abstract book, each highlighting a special fusion of technical skill and creativity. I kindly invite you to browse these pages, which celebrate the accomplishments of our future professionals. Welcome once more to the Exhibition of Electrical, Electronic, and System Engineering. I hope the knowledge found in these pages helps to motivate and clear the way for the upcoming generation of creative engineers.